Overview of Fungal Infections - The Italian Experience - Bassetti, Matteo; Righi, Elda (Seminars in Respiratory and Critical Care Medicine, 2015)
The incidence of severe fungal infections has increased worldwide and represents a serious threat, especially among immunocompromised and critically ill patients. Most common pulmonary fungal infections include aspergillosis, cryptococcosis, and Pneumocystis jiroveci pneumonia. Among nosocomial bloodstream infections, Candida spp. is the most common isolated fungus. Mortality rates up to 60% in critically ill patients with Candida infections and 90% in hematological patients with invasive aspergillosis are reported. Furthermore, fungal infections contribute to high morbidity and prolonged hospitalizations. Since standard cultural methods can show low sensitivity or provide delayed responses, new non–culture-dependent methods such as galactomannan β-D-glucan are now available. Novel antifungal compounds (e.g., amphotericin B lipid formulations, last-generation azoles, and echinocandins) have been introduced in the recent years. Nevertheless, despite new advances the appropriate use of diagnostic assays along with a thorough therapeutic management remain the key to ensure an early appropriate targeted treatment that represents the crucial factor to attain a successful approach to severe fungal infections.
Keywords: fungal infections; aspergillosis; Candida; Pneumocystis jiroveci pneumonia; cryptococcosis; antifungal treatment